The effect of quinoline anti-malarial drugs on the endolysosomal and secretory pathways of plasmodium falciparum strain 3D7, dictyostelium discoideum and mammalian A549 cells - Roberts, Lindi (Division of Clinical Pharmacology, 2014)
Includes bibliographical references (leaves 92-109).